Prescription patterns of doctors in rural settings of district Peshawar, Pakistan: A descriptive cross-sectional study - Khan, Mashal; Marwat, Muhammad Imran; Muhammad Osama; Elahi, Savaira (Journal of the Pakistan Medical Association, 2026)
Objectives: To analyse prescriptions with respect to the essential components of a standard prescription format, and to compare them with global standards. Method: The descriptive cross-sectional study was conducted from December 2022 to April 2023 after approval from the ethics review board of Khyber Medical College, Peshawar, Pakistan, at eight private clinics in rural areas of the district. Data was collected by taking pictures of prescriptions. They were analysed for the five essential components of prescriptions; patient identifiers, superscriptions, inscriptions, transcriptions and prescriber identifiers. Additionally, the prescriptions were compared against the prescribing indicators outlined by the World Health Organisation/International Network for Rational Use of Drugs. Data was analysed using SPSS 24. Results: Of the 377 prescriptions analysed, 231(61.3%) contained all the five essential components, while 70(18.6%), 203(53.8%) and 146(38.7%) prescriptions recorded vital signs, diagnoses and investigations, respectively. There were 253(53.1%) prescriptions with antibiotics, 252(66.8%) with painkillers, 36(9.5%) with steroids, 128(34.0%) with injections, 19/1195(1.6%) drugs prescribed by generic names, and 1063/1195(89.0%) from the essential medicine list. None of the prescriptions met the indicators recommended by the World Health Organisation/International Network for Rational Use of Drugs. Conclusions: Practitioners showed poor compliance with the standard prescription format, and overlooked the importance of recording vital signs and diagnoses. Moreover, World Health Organisation/International Network for Rational Use of Drugs recommendations were poorly followed, suggesting suboptimal prescriptions. Key Words: Drug prescribing, Prescription components, Prescription indicators, Drug usage, Drug adherence.